Volumetric behaviour of subsurface ground due to tunnelling in completely drained granular soil. (December 2019) - Zheng, Gang; Ge, Longbo; Zhang, Tianqi; Sun, Jibin; Fan, Qi; Tong, Jingbo
Abstract: In this article, numerical modelling was first conducted to investigate the volumetric behaviour of the subsurface ground in a physical model test that imitated the tunnelling process in a loose sand. A new volumetric response mechanism of the subsurface ground was revealed in which the effects of the soil stress path are of particular note. A parametric study was then performed to investigate the effects of relative density of soil, cover-to-depth ratio and displacement patterns around the tunnel on the resulting soil volume loss. The mechanisms by which these factors affect the volumetric behaviour of the subsurface ground were clarified.